Adsorptive and photocatalytic performance of perovskite material for the removal of food dye in an aqueous solution - Debnath, Abhijit (Science Direct, 2021)
Lanthanum cerate (La2Ce2O7), a perovskite nanomaterial, has been synthesized by using the gel combustion method to remove carcinogenic and neurotoxic dye FD&C Yellow 5 from its aqueous solution and the same has been also explored to investigate the photocatalytic behavior towards the degradation of food dye. The synthesized material has been extensively characterized using various techniques such as XRD, FT-IR, SEM, BET surface area and through pHZPC. The effect of various operational parameters like solution pH, temperature, and initial dye concentration were investigated to explore the optimum dye removal percentage. To gain the mechanistic perceptive of the dye removal process, various kinetic models were used. Pseudo-second order kinetic model was found to be well suited in describing the sorption system. The intra-particle diffusion model suggested that the film diffusion process controls the overall rate of the dye and perovskite interaction process. Further, equilibrium data interpretation was appraised through various isotherm models and adsorption data found to be consistent with the Freundlich model suggesting multilayer coverage of dye species over the surface of perovskite particles and maximum adsorption capacity was evaluated as 133.3 mg/g at 323 K. Thermodynamic parametric investigation indicated that the dye adsorption process was feasible, spontaneous and endothermic. The activation energy of the adsorbate-adsorbent interaction process was found to be 5.26 kJ/mol, suggesting a physisorption mechanism governs the adsorption process. Photocatalytic efficiency of the perovskite was also scrutinized for dye concentrations 10, 25 and 50 mg/L and dye degradation of 89%, 75% and 69% was observed for each tested concentrations, respectively
Keywords: Perovskite; Food; dye; Adsorption; Mass transfer; Photocatalytic; degradation